Health Policy in Nepal: An Assessment of Clinical Guidelines in Relation to the Burden of Disease - Hodgkinson, Sara; Saddiq, Muhammad; Balen, Julie (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Clinical guidelines provide health workers with valuable information on how to diagnose and treat patients. In many low-income countries, there appears to be a lack of appropriate clinical guidelines for conditions with high rates of morbidity; Nepal is one such nation. It is useful to examine clinical guidelines in relation to disease burden to establish any gaps which might be addressed through changes in policy and practice.Methods: The research adopted a mixed-methods approach, quantifying disease burden both nationally and in five districts served by PHASE Nepal – an NGO working in health and development – before contrasting this with available clinical guidelines in Nepal.  Key informant interviews were subsequently conducted to gain greater insight into disease burden and guideline availability.Results: Of the 10 diseases found to be most burdensome in the PHASE-served districts, 3 lacked any context-specific guidelines. NCDs were found to be prevalent at both district and national level, yet guideline provision for such conditions was minimal. Mental illness was highlighted by interview participants as a growing problem; however, Nepal does not currently have any utilisable clinical guidelines for mental health. Missing data was identified as a significant issue, with lack of mortality data hindering accurate quantification of local and national disease burden.Conclusions: There is evident need for more context-appropriate clinical guidelines in Nepal to effectively diagnose and treat diseases that are most burdensome within communities. Improving health data quality is fundamental to ensuring policy makers are equipped with accurate information from which to develop appropriate protocol.Journal of Manmohan Memorial Institute of Health SciencesVol. 3, No. 1, 2017, page: 24-35